Sensitive to Infection but Strong in Defense-Female Sex and the Power of Oestradiol in the COVID-19 Pandemic - Louise Newson; Isaac Manyonda; Rebecca Lewis; Robert Preissner; Saskia Preissner; Ute Seeland (Frontiers Media S.A., 2021)
The incidence of SARS-CoV2 infections is around 15% higher in premenopausal women compared to age matched men, yet the fatality rate from COVID-19 is significantly higher in men than women for all age strata. Sex differences have also been observed in recent epidemics including severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), with SARS-CoV 2 virus infection sex differences appear more dramatic. The regulation and expression of the angiotensin converting enzyme 2 (ACE2) is the key for this special coronavirus SARS-CoV-2 to enter the cell. 17β-oestradiol increases expression level and activity of angiotensin converting enzyme-2 (ACE2) and the alternative signaling pathway of Ang II via the angiotensin II receptor type II (AT2R) and the Mas receptor is more dominant in female sex than in male sex. Maybe a hint to explain the higher infection risk in women. The same hormonal milieu plays a major role in protecting women where morbidity and mortality are concerned, since the dominant female hormone, oestradiol, has immune-modulatory properties that are likely to be protective against virus infections. It is also known that the X chromosome contains the largest number of immune-related genes, potentially conferring an advantage to women in efficient immune responsiveness. Lifestyle factors are also likely to be contributory. Premenopausal women could possibly face higher exposure to infection (hence higher infection rates) because economic conditions are often less favorable for them with less opportunity for home office work because of jobs requiring mandatory attendance. Due to the additional task of childcare, it is likely that contact times with other people will be longer. Women generally make healthier lifestyle choices, thus reducing the disease burden that confers high risk of mortality in COVID-19 infected men. This narrative review aims to present key concepts and knowledge gaps on the effects of oestrogen associated with SARS-CoV2 infection and COVID-19 disease.